Moths ordbog og dens virkningshistorie - Nielsen, Marita Akhøj (LexicoNordica, 2016)
Matthias Moth (1649-1719) worked out the earliest comprehensive dictionary of Danish, based on collections of words and sayings, predominantly of ordinary people’s daily language. The final edition contains 109,096 headwords. Danish is the core of the dictionary, but is accompanied by Latin equivalents. The dictionary was not published until 2013 and is now online. During 300 years the manuscript has served as an important source for later Danish dictionaries, and Moth’s impact is examined in the paper, especially with regard to Videnskabernes Selskabs Ordbog (1793-1905), Chr. Molbech’s Dansk Ordbog (1833), Otto Kalkar’s Ordbog til det ældre danske sprog (1881-1918) and Ordbog over det danske Sprog (1918-56).